Fetal bovine serum (FBS): past - present - future - Van der Valk, Jan; Bieback, Karen (Alternatives to animal experimentation, 2018)
The supplementation of culture medium with fetal bovine serum (FBS, also referred to as “fetal calf serum”) is still common practice in cell culture applications. Due to a number of disadvantages in terms of quality and reproducibility of in vitro data, animal welfare concerns, and in light of recent cases of fraudulent marketing, the search for alternatives and the development of serum-free medium formulations has gained global attention. Here, we report on the 3rd Workshop on FBS, Serum Alternatives and Serum-free Media, where regulatory aspects, the serum dilemma, alternatives to FBS, case-studies of serum-free in vitro applications, and the establishment of serum-free databases were discussed.The whole process of obtaining blood from a living calf fetus to using the FBS produced from it for scientific purposes is de facto not yet legally regulated despite the existing EU-Directive 2010/63/EU on the use of animals for scientific purposes. Together with the above-mentioned challenges, several strategies have been developed to reduce or replace FBS in cell culture media in terms of the 3Rs (Refinement, Reduction, Replacement). Most recently, releasates of activated human donor thrombocytes (human platelet lysates) have been shown to be one of the most promising serum alternatives when chemically-defined media are not yet an option. Additionally, new developments in cell-based assay techniques, advanced organ-on-chip and microphysiological systems are covered in this report. Chemically-defined serum-free media are shown to be the ultimate goal for the majority of culture systems, and examples are discussed.